Measurement of compressibility by means of pressure-bulk modulus relationship for low-to-high viscosity oils - Sulaiman, Mohd Hafis; Christiansen, P.; Bay, N. (Malaysian Tribology Society, 2018)
The accurate compressibility of liquid lubricants at varying pressures to studying the importance of surface topography and lubrication in metal forming has led to construction and testing of an experimental tool setup for measuring compressibility of fluids by means of pressure-bulk modulus relationship for low-to-high viscosity oils. Testing of mineral oils showed a nonlinear relationship between the bulk modulus and the pressure for measuring compressibility of fluids up to a pressure of 500 MPa.